El Ni\~no and Indian droughts: A scoping exercise - Shweta Saini; Ashok Gulati (Indian Council for Research on International Economic Relations (ICRIER), 2014)
Weather experts around the world are foreseeing a strong El Ni\~no in 2014. In India, these developments are feared to lead to droughts. In the last 14 years, out of the four El Ni\~no years globally, three resulted in Indian droughts. Since the 1980s, all the six droughts faced by India were in El Ni\~no years but not all El Ni\~no years led to drought situations in the country. The paper approaches the question of disconnect between El Ni\~no and Indian droughts by exploring the timing of El Ni\~no developments in a year and its relation with monsoon rains. We construct an India specific El Ni\~no (ISEL), based on tracking temperature anomalies of three months moving averages for specific months (April-May-June to September-October-November), captured in the Oceanic Ni\~no Index (ONI). The choice of these months is dictated by the fact that June-September rainfall months must be part of three monthly moving ONI anomalies, either as the ending month or beginning month. ...
Keywords: Q18; Q25; Q28; Q54; F64; Q58; 330; Indian Agriculture; Climate Change; El Ni\~no; Drought; Irrigation; 2014